Legal Analysis Of The Implementation Of Risk Allocation In Cooperation Schemes With The Government And Business Entities In Infrastructure Provision In Indonesia - Rezkyna, Nabilah; Faisal, Pupung; Trisnamansyah, Purnama (JURNAL LEGALITAS, 2021)
Risk allocation is a key feature in government-business partnerships. In the Public Private Partnership scheme, risk allocation is a difficult thing. The transfer of risk to the private sector has an impact on the price of the project. Likewise, allocating risk to the public sector which in practice tends to reduce Value For Money. In addition, project risk is dynamic and changes throughout the life of the project so it cannot be predicted with certainty. This normative research aims to examine the guiding principles for increasing the effectiveness of risk allocation and maximizing Value For Money from existing regulations in Indonesia and Government Cooperation agreements with Business Entities based on best practices in several other countries. The approach used in this paper uses a conceptual and comparative approach. The results obtained from this paper are that it is necessary to identify and anticipate risks including alternative solutions that are adjusted to the principle of risk allocation to minimize risk, as well as adjustments to the matrix that have been made by PT PII, risk allocation principles, best practices and related regulatory frameworks in Indonesia. Result, risks in KPBU projects are often an obstacle in the success of KPBU implementation in Indonesia. To minimize the risks that will be faced or may be faced, it is necessary to identify and anticipate risks including alternative solutions that are adjusted to the principle of risk allocation. In developing an effective risk matrix, innovative thinking is needed that is adapted to the characteristics of the KPBU project and the principles of risk management. This must also be adjusted to the matrix that has been made by PT PII, the principles of risk allocation, best practices and related regulatory frameworks in Indonesia are used as references. If properly implemented, this principle is expected to result in a lower risk premium and lower project costs, thus having a positive impact on the project's stakeholders.